The importance of mother-child interaction on smart device usage and behavior outcomes among toddlers: a longitudinal study - Pairote Chakranon; Jian-Pei Huang; Heng-Kien Au; Chen-Li Lin; Yi-Yung Chen; Shih-Peng Mao; Wen-Yi Lin; Ming-Lun Zou; Wanda Estinfort; Yi-Hua Chen (BMC, 2024)
Abstract Background In recent years, smart devices have become an integral part of daily life. However, longitudinal studies, particularly those regarding the relationship between toddlers' smart device usage and behavioral outcomes, are limited. Understanding the impact of parent-child interactions on this relationship is crucial for enhancing toddlers' developmental outcomes. Accordingly, this study examined the influence of early screen time and media content exposure on toddlers' behaviors, as well as the positive effects of mother-child interactions on this influence. Methods We used relevant data related to 277 children born between November 2016 and July 2020 and who were part of an ongoing prospective follow-up study conducted across five hospitals in Taipei City, Taiwan. We analyzed (1) data from maternal reports regarding children's behavior by using the Child Behavior Checklist (for ages 11/2-5 years), (2) assessments of mother-child interactions by using the Brigance Parent-Child Interactions Scale, and (3) self-reported parental data covering the first 3 postpartum years. Statistical analyses involved group-based trajectory modeling and multiple linear regression. Results A considerable increase in screen time between the ages of 1 and 3 years was associated with less favorable behavioral outcomes at age 3. These outcomes included somatic complaints [adjusted beta coefficient (aβ) = 2.17, 95% confidence interval (CI) = 0.39-3.95, p-value = 0.01], withdrawal (aβ = 2.42, 95% CI = 0.15-4.69, p-value = 0.04), and aggressive behavior (aβ = 6.53, 95% CI = 0.25-12.81, p-value = 0.04). This association was particularly evident among children with lower levels of mother-child interaction. Nevertheless, positive mother-child interactions mitigated most of the adverse effects. Additionally, increased exposure to games and cartoons was associated with poorer behavioral outcomes in all children except for those experiencing positive mother-child interactions. Conclusion Early mother-child interactions play a crucial role in mitigating the risk of behavioral problems in toddlers who spend prolonged periods looking at screens and who are frequently exposed to game and cartoon content.